2020
DOI: 10.1186/s12957-020-1782-6
|View full text |Cite
|
Sign up to set email alerts
|

Fecal incontinence after total mesorectal excision for rectal cancer—impact of potential risk factors and pelvic intraoperative neuromonitoring

Abstract: Background: Fecal incontinence frequently occurs after total mesorectal excision for rectal cancer. This prospective study analyzed predictive factors and the impact of pelvic intraoperative neuromonitoring at different follow-up intervals. Methods: Fifty-two patients were included undergoing total mesorectal excision for rectal cancer, and 29 under control of pelvic intraoperative neuromonitoring. Fecal incontinence was assessed using the Wexner Score at 3 and 6 months after stoma closure (follow-ups 1 and 2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…Kauff and Kneist et al, who have published research on pelvic neuromonitoring since 2011, have also reported the usage of the stimulation frequency of 30 Hz in several studies. Stimulation currents in the range of 1–25 mA were described 19 , whereby a current of 6 mA was applied in most studies 20 , 21 , 26 , which also corresponds to the approach in this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kauff and Kneist et al, who have published research on pelvic neuromonitoring since 2011, have also reported the usage of the stimulation frequency of 30 Hz in several studies. Stimulation currents in the range of 1–25 mA were described 19 , whereby a current of 6 mA was applied in most studies 20 , 21 , 26 , which also corresponds to the approach in this study.…”
Section: Discussionmentioning
confidence: 99%
“…A series of studies has been published fby the research group Kauff and Kneist et al 15 , 20 , 23 . Recently published studies indicate that pelvic intraoperative neuromonitoring performed with cystomanometry and EMG of the IAS is associated with lower rates of new-onset urinary dysfunction and fecal incontinence 21 , 26 . The practical application of this method requires filling the urinary bladder with Ringer’s solution for cystomanometry and precise positioning of the electrodes on the internal anal sphincter, which has to be performed under endosonography in case needle electrodes are used 29 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the light of these considerations, to improve the QOL of patients submitted to CRS plus HIPEC, it is important to not only cure the psychological aspect but also reduce the consequences of the pelvic innervation related to the pelvic peritonectomy. For this reason, based on the well-coded experiences in rectal surgery [ 4 ], [ 10 ], [ 11 ], we decided to apply IONM to CRS plus HIPEC. We retain that IONM is technically feasible during peritonectomy and that it can help preserve pelvic nerves.…”
Section: Discussionmentioning
confidence: 99%
“…Kauff et al compared pelvic IONM during TME with a control group and demonstrated the less new onset of faecal incontinence in the neuromonitoring group at each follow-up (3, 6. 12 and 24 months) [ 123 ]. Zhou et al demonstrated no difference between preoperative and postoperative urogenital and anorectal function in patients with positive IONM.…”
Section: Introductionmentioning
confidence: 99%